Generation Z : does climate concern match knowledge? - Isaacs, Andrew; Coromina, Natàlia Costa I. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
In Fall 2020, researchers tested how much graduate students at UC Berkeley's Haas School of Business understood about climate change science. About 144 MBA students took a 4-minute "pop quiz" with eight short questions gauging their general familiarity with climate change. While the quiz was not comprehensive, the results indicated students' basic knowledge was limited.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Climatic changes